Low-temperature sintered Ba16ZrNb12O48-BaWO4 composite ceramics with near-zero τf and enhanced Q×f for LTCC applications - Yu, Zhen Fa; Wang, Chang Hao; Wang, Xin; He, Guoqiang; Ma, Peiwen; Bao, Jian; Fang, Zhen; Xu, Di Ming; Pang, Li Xia; Zhou, Tao; Tan, Kar Ban; Zhou, Di (Elsevier, 2025)
Perovskite-structured ceramics are promising for their tunable properties, while LTCC technology requires low sintering temperatures and near-zero τ f . BaCu(B4O8) as a sintering aid reduced Ba16ZrNb12O48’s sintering temperature from 1450 ℃ to 1000 ℃. A two-phase strategy designed (1 − x )Ba16ZrNb12O48- x BaWO4 + 5 wt% BaCu(B4O8) ( x = 0.88–0.93) ceramics for τ f modulation. Ba16ZrNb12O48 with 5 wt% BaCu(B4O8) densified at 1000 ℃, yielding ε r = 32.6, Q×f = 22,400 GHz, τ f = +44.2 ppm/℃, and ρ bulk = 5.83 g/cm3. Notably, x = 0.92 with 5 wt% BaCu(B4O8), co-fired at 950 ℃ and annealed, achieved τ f = +7.4 ppm/℃ (near-zero), Q×f = 29,100 GHz, and ε r = 20.0. XRD/SEM-EDS confirmed chemical inertness and no Cu diffusion at the ceramic/electrode interface. These features make it a promising LTCC candidate.